Poly(lactic acid)-poly(ethylene glycol) copolymers for use as drug delivery systems - Hagan, Susan Anne (1998)
Block copolymers of polylactide and poly( ethylene glycol) (PLA-PEG) were investigated as biodegradable drug delivery systems. They are defined by the differing molecular weight ratios of polylactide to poly( ethylene glycol). Copolymers containing more hydrophilic PEG than hydrophobic PLA per molecule self-dispersed in water giving spherical nonionic micelles. Purification by gel permeation chromatography gave two peaks. The first peak only formed micelles (the second was PLA-depleted). Analysis by dynamic light scattering (DLS) and transmission electron microscopy (TEM) gave diameters of IS.6nm and 18.9nm for 1.5:2 and 2:5 PLA-PEG micelles respectively.